WELFARE NORMS FOR SWINE PRODUCTION UNDER INTENSIVE REARING SYSTEM - SILVA, RAQUEL B. T. R. DA; NÄÄS, IRENILZA A.; MOURA, DANIELLA J.; SILVEIRA, NEIDIMILA A. (Revista Brasileira de Engenharia de Biossistemas, 2007)
Animal welfare is today one of the most important non-regulated commercial barrier inanimal protein international trade. The European Union along with the United States ofAmerica and Australia are important pork exporters. Rearing conditions vary betweencountries as it depends on the climate, as well as these animals transportation is alsodistinct worldwide. This research had the objective of describing a scenario related tolegal demands determined by the presence of adopted norms or legislations. For thisevaluation critical items were elected and score were given varying from 1 to 5 (very badto very good) as a function of the existence and the adoption of norms for each item.Average values were calculated and mean comparative analysis was applied in order toenhance the specific gaps. Results show that the countries in the European Union, theUnited States and Australia have already made and adopted their norms and laws thataim attending to certain welfare demands; while Brazil shows to be behind. Because ofthe new international animal welfare demands there is a need to update Brazilian legislation,as the country is an important pork exporter.